Peran Lamborghini dalam Mendukung Aksesibilitas Wisata di Kawah Ijen - Akwila Nathanael Odoh; Mochamad Amboro Alfianto; Muhammad Alandra Bestama; Maleda Littler; Ayla Hanifa Nur Ramadhani; Maulana Hasan As'ariy; Ridwan Robbani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study aims to examine in depth the role of traditional cart taxis in supporting tourism accessibility in Ijen Crater. Cart taxis as a local community-based transportation mode have a significant contribution in addressing geographical challenges and limited formal infrastructure in natural tourism areas. Through a qualitative descriptive approach based on observation, documentation, and literature studies, it was found that traditional cart taxis not only function as a means of transportation, but also as social and economic agents that strengthen community involvement in the tourism industry. Traditional taxi activities also provide alternative livelihoods, create authentic interactions with tourists, and support the microeconomic ecosystem at the local level. However, traditional taxi drivers face serious challenges such as income uncertainty, unclear legal status, and minimal policy support. This study recommends the importance of integrating traditional cart taxis into an inclusive, participatory, and sustainable tourism management system.